Varietal assessment of chrysanthemum (Dendranthema grandiflora) under south Gujarat agro-climatic conditions (Current Horticulture, 2024)
The study was carried out to evaluate 20 varieties of chrysanthemum (Dendranthema grandiflora Tzvelev) for three years, viz. 2009-10, 2010-11 and 2011-12 in rabi season. Wide variations were recorded in growth, flowering and yield parameters. The maximum plant height (58.27 cm) and branches/plant (11.91) were recorded in Ratlam Selection, while Maghi recorded maximum plant spread (39.94 cm). The Harvest recorded earliest flowering (63.38 days), whereas maximum flowering duration (60.22 days) was found in Ravi Kiran. Significantly maximum diameter of flower (8.55 cm) and weight of 10 flowers (47.96 g) were recorded in Miss India. Variety Maghi gave highest number of flowers/plant (133.78), whereas Silk Brocade recorded maximum flower yield (200.29 g/plant and 288.44 q/ha). Dolly White recorded maximum vase-life (11.44 days), whereas IIHR-6, Miss India, Shyamal, CS-16 and Yellow Gold were found sensitive to aphid. The highest net realization as well as Benefit: Cost Ratio were recorded by Ratlam Selection because of higher price due to white colour and good quality flowers which are in more demand.
Keywords: Varieties; Flower diameter; Vase-life; Variation